1991
DOI: 10.1159/000168304
|View full text |Cite
|
Sign up to set email alerts
|

Serum Hyaluronic Acid and Procollagen III Amino Terminal Propeptide in Chronic Renal Failure

Abstract: Elevated serum concentrations of hyaluronic acid (HA) and procollagen III amino terminal propeptide (PIIINP) have been found in various diseases characterized by altered metabolism of collagen. In the present study, their serum levels were measured in 105 renal patients and 22 normal controls. Median HA concentrations were 23 µg/l in controls, 47 µg/l in patients with chronic renal failure (CRF, not on dialysis; p < 0.001), 75 ug/l on CAPD (p < 0.001 vs. controls, p = 0.045 vs. CRF), and 167 µg/l on hemodialys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 13 publications
4
13
1
Order By: Relevance
“…The data in the present study confirm that patients with various chronic renal disease have increased PI 11N P [14,15]. When comparing serum PIIINP in the kidney-transplanted patients to the levels in patients with chronic renal disease it should be considered that all of the renal graft recipients except one received prednisolone, which in similar doses has been shown to reduce serum levels of PIIINP and PICP significantly [24].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The data in the present study confirm that patients with various chronic renal disease have increased PI 11N P [14,15]. When comparing serum PIIINP in the kidney-transplanted patients to the levels in patients with chronic renal disease it should be considered that all of the renal graft recipients except one received prednisolone, which in similar doses has been shown to reduce serum levels of PIIINP and PICP significantly [24].…”
Section: Discussionsupporting
confidence: 79%
“…From previous studies it is known that serum PIIINP may be increased in various renal diseases most likely as a result of increased renal fibrosis [14,15], The patients enrolled in the present study did not suffer from other conditions known to be related to increased fibrogenesis, such as arthritis or fibrosis of the liver. Some of the patients had native kidneys(s) in situ, which might be considered to contribute to the in creased serum PIIINP.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Alternatively, these hyaluronidases could play a role in the metabolism of circulating HA. That the kidney could play a major role in the disposal of HA is supported by the observation that patients with renal failure display elevated levels of HA [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…0.001). Honkanen et al [7] reported that the serum hyaluronic acid concentrations were increased in patients on hemodialysis, but that there were no differences in serum KL-6 levels between hemodialysis patients without lung disease and healthy controls. The serum KL-6 concentrations in our patients following hemodialysis showed no change in comparison with the concentrations before hemodialysis.…”
mentioning
confidence: 99%